Pedagogical Strategies of Islamic Religious Education Teachers in Developing Students' Higher Order Thinking Skills (HOTS) - Ulul Azmi Al ghozi; Kustiana Arisanti; Ummi Lailia Maghfiroh (Journal of Educational Management Research, 2026)
This study aims to examine the instructional strategies employed by Islamic Religious Education (PAI) teachers to develop Higher Order Thinking Skills (HOTS) and to identify the supporting and inhibiting factors influencing their implementation. A qualitative case study was conducted at Madrasah. Data were collected through non-participant observation, semi-structured interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal six key instructional strategies: active learning, higher-order questioning, contextual learning, interactive discussion, diverse learning resources, and HOTS-based assessment. The implementation of these strategies was supported by teachers' pedagogical competence, adequate instructional resources, and a conducive learning environment, while limited instructional time, heterogeneous student readiness, and conventional teaching practices emerged as major constraints. The study concludes that the successful development of HOTS requires an integrated instructional approach combining planning, implementation, classroom interaction, and authentic assessment. This research contributes a comprehensive pedagogical framework for HOTS-oriented Islamic Religious Education and provides practical recommendations for teachers, school leaders, and policymakers to strengthen instructional quality.